تقوية القدرة التركيبية اللغة العربية من خلال تعليم كتاب النحو الواضح في المدرسة الثانوية الإسلامية المحمدية بورووكرتو - Barotut Takiyah; Ali Muhdi (Study Program of Arabic Language Education (PBA), 2026)
Arabic language instruction in Islamic schools plays a vital role in helping students understand Islamic teachings derived from Arabic texts. One of the fundamental competencies that students need to master is syntactic ability (nahw), as it is directly related to understanding sentence structure and meaning. In classroom practice, however, nahw is often perceived as difficult and less meaningful, which affects students’ motivation and self-confidence. This study aims to describe how learning through the book Nahwu Al-Wadih strengthens students’ Arabic syntactic ability at MA Muhammadiyah Purwokerto. The research employed a qualitative descriptive approach with a field research design. Data were collected through classroom observations, interviews with teachers and students, and analysis of instructional documents. The findings indicate that the learning of Nahwu Al-Wadih was implemented systematically through the stages of planning, implementation, and evaluation. The inductive approach applied in the learning process helped students understand syntactic rules through concrete examples that were closely related to their learning experiences. The results show that this learning contributed positively to improving students’ ability to identify sentence elements, determine grammatical functions, and understand syntactic relationships in Arabic sentences. Overall, the learning of Nahwu Al-Wadih offered a more meaningful and humanistic approach to teaching nahw, despite challenges related to limited instructional time and differences in students’ abilities.Keywords: syntactic ability; nahw instruction; Nahwu Al-Wadih; Arabic language.